2022
DOI: 10.1111/pde.15180
|View full text |Cite
|
Sign up to set email alerts
|

The co‐occurrence of segmental vitiligo and linear morphea in a pediatric patient and a review of the literature

Abstract: Linear morphea and segmental vitiligo are both autoimmune diseases that are observed in the pediatric population, with rare reports of their co-existence. We describe a case of linear morphea and segmental vitiligo with an overlapping distribution in a pediatric patient and review the literature. Including our own case, we summarize 10 cases of co-occurring segmental vitiligo and morphea in pediatric patients; most of these lesions follow a blaschkolinear distribution, and none of the patients had autoimmune t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Furthermore, the coexistence of morphea and segmental vitiligo within the framework of PAI has been documented, especially in the pediatric population. Notably, these lesions often follow a Blaschko linear distribution, suggesting genetic mosaicism (21). Dervis et al reported another instance of MAS characterized by the combination of morphea, vitiligo, and autoimmune thyroid disease (22).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the coexistence of morphea and segmental vitiligo within the framework of PAI has been documented, especially in the pediatric population. Notably, these lesions often follow a Blaschko linear distribution, suggesting genetic mosaicism (21). Dervis et al reported another instance of MAS characterized by the combination of morphea, vitiligo, and autoimmune thyroid disease (22).…”
Section: Discussionmentioning
confidence: 99%